Effect of partial shading in grid connected solar PV system with FL controller - K Latha Shenoy; C. Gurudas Nayak; Rajashekar P. Mandi (Institute of Advanced Engineering and Science, 2021)
As conventional fossil fuel reserves shrink and the danger of climate change prevailing, the need for alternative energy sources is unparalleled. A smart approach to compensate the dependence on electricity generated by burning fossil fuels is through the power generation using grid connected PV system. Partial shading on PV array affects the quantity of the output power in photovoltaic (PV) systems. To extract maximum power from PV under variable irradiance, variable temperature and partial shading condition, various MPPT algorithms are used. Incremental conductance and fuzzy based MPPT techniques are used for maximum power extraction from PV array. Basically 11 kW Solar PV system comprising of PV array coupled with an Inverter through a dc-dc converter is considered for the analysis and output of the inverter is supplied to the load through the LCL filter. An Intelligent controller for maximum power point tracking of PV power is designed. Also, a fuzzy controller for VSC is developed to improve the system performance. The above proposed design has been simulated in the MATLAB/Simulink and analyzed the system performance under various operating conditions. Finally, the performance is evaluated with IEEE 1547 standard for showing the effectiveness of the system.